What types of capital flows help improve international risk sharing? - Ergys Islamaj; M. Ayhan Kose (Koç University-TÜSIAD Economic Research Forum (ERF), 2021)
Cross-border capital flows are expected to lead to increased international risk sharing by facilitating borrowing and lending in global financial markets. This paper examines risk-sharing outcomes of various types of capital flows (foreign direct investment, portfolio equity, debt, remittance, and aid flows) in a large sample of emerging market and developing economies. The results suggest that remittances and aid flows are associated with increased international risk sharing. Other types of capital flows are not consistently correlated with better risk-sharing outcomes. These findings are robust to the use of different econometric specifications, country-specific characteristics, and other controls.
Keywords: E1; F02; F4; G01; 330; capital flows; remittances; aid flows; international risk sharing